Endothelial Response to Glucocorticoids in Inflammatory Diseases - Zielińska, Karolina A.; Van Moortel, Laura; Opdenakker, Ghislain; De Bosscher, Karolien; Van den Steen, Philippe E. (Frontiers in Immunology, 2016)
The endothelium plays a crucial role in inflammation. A balanced control of inflammation requires the action of glucocorticoids (GCs), steroidal hormones with potent cell-specific anti-inflammatory properties. Besides the classic anti-inflammatory effects of GCs on leukocytes, recent studies confirm that endothelial cells also represent an important target for GCs. GCs regulate different aspects of endothelial physiology including expression of adhesion molecules, production of pro-inflammatory cytokines and chemokines and maintenance of endothelial barrier integrity. However, the regulation of endothelial GC sensitivity remains incompletely understood. In this review, we specifically examine the endothelial response to GCs in various inflammatory diseases ranging from multiple sclerosis, stroke, sepsis and vasculitis to atherosclerosis. Shedding more light on the cross-talk between GCs and endothelium will help to improve existing therapeutic strategies and develop new therapies better tailored to the needs of patients.